THE QUR'AN, DIGITAL TOOLS AND THE TRANSFORMATION OF RELIGIOUS MEDIA - Samsul Ariyadi (PT. Jurnal Center Indonesia Publisher, 2025)
This study examines the development of Al-Quran digital tools and their impact on Islamic learning in the context of religious media transformation. The study was conducted with a qualitative approach, using the documentation study method and content analysis of the Al-Quran mobile application available on Android and iOS platforms within the last five years. The analysis is focused on aspects of usability, accessibility, and digital features that support learning and understanding of the Quran. The findings of the study reveal that the integration of digital technology and religious content has resulted in a new paradigm in the learning and dissemination of Islamic messages, marking social change and increased transformation of religious media. This research produces a comprehensive evaluation framework for Al-Quran digital tools and typologies based on categories and functionality, which makes theoretical and practical contributions to the development of Al-Quran mobile applications in the future.